2017
DOI: 10.1007/s10796-017-9816-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Organisational Competitiveness Via Social Media - a Strategy as Practice Perspective

Abstract: The affordances, popularity and pervasive use of social media platforms such as Facebook, Twitter and Instagram have made these platforms attractive to organisations for enhancing their competitiveness and creating business value. Despite this apparent significance of social media for businesses, they are struggling with the development of a social media strategy as well as understanding the implications of social media on practice within their organisations. This paper explores how social media has become a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 56 publications
(97 reference statements)
0
42
0
4
Order By: Relevance
“…The results of this study show that social media is having an impact on competitiveness through imitation and product development. The results reported in this study also suggest how social media affects the practices within an organisation, consequently making the social media strategy an emergent phenomenon (Kwayu et al 2018).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The results of this study show that social media is having an impact on competitiveness through imitation and product development. The results reported in this study also suggest how social media affects the practices within an organisation, consequently making the social media strategy an emergent phenomenon (Kwayu et al 2018).…”
mentioning
confidence: 51%
“…The first three articles of this special issue have adopted a qualitative approach to examine issues of self-disclosure (Richey et al 2018), organisational competitiveness (Kwayu et al 2018), and tackling and improving Big Data of variable data quality (Wahyudi et al 2018).…”
mentioning
confidence: 99%
“…Kwayu et al 2017;Neeley and Leonardi 2018;Zammuto et al 2007). Kwayu et al 2017;Neeley and Leonardi 2018;Zammuto et al 2007).…”
Section: A Relational Perspective On Agencymentioning
confidence: 99%
“…In our review, we identified a few articles adopting a relational view on agency (e.g. Kwayu et al 2017;Neeley and Leonardi 2018;Zammuto et al 2007). These do not favour human agency but cultivate an analytical sensibility to other agencies.…”
Section: A Relational Perspective On Agencymentioning
confidence: 99%
“…Compared with traditional communication tools, social media enable organizations to bypass the trade-off between univocality and multivocality, reach and richness, and production and consumption (Huang et al 2013). Furthermore, they allow organizations to engage in timely, open, and interactive conversations with customers at relatively-low costs (Kaplan and Haenlein 2010;Kwayu et al 2018). As such, they are particularly appealing to SMEs because SMEs are notoriously short of resources and funding (Järvinen et al 2012).…”
Section: Introductionmentioning
confidence: 99%